The most European place in St. Petersburg: the Museum of Anthropology and Ethnography between the Past and the Future - Efim Rezvan (EtnoAntropologia, 2018)
The article presents a short survey of the history of Peter the Great Museum of Anthropology and Ethnography (Kunstkamera) of the Russian Academy of Sciences (MAE RAS). Today MAE RAS is one of the largest and oldest ethnographic museums in the world. The richest scientific collections of MAE RAS (today more than 1.2 million units of storage) consistently evolved throughout its 300-year history primarily as a result of intensive expeditionary and research activities of the Academy of Sciences. The history of Russia in the last three hundred years is also the history of the Museum. It shared with the country the breakthrough of the Peter the Great and Catherine epochs, the great achievements for Russian science and culture of the 19th century, the achievements of the “great era” of Soviet academic science. The museum remembers the years of Great terror, the horrors of the Siege of Leningrad, and the difficult times after the collapse of the USSR. The priority of science in the system of state values, the study and preservation of national cultures and interethnic dialogue are the key aspects of the Museum's activities. They always coincided and coincide today with the most important tasks of Russian statehood.